SKDI-Based Needs Analysis for Designing English for Students of Medicine in Indonesia - Sujana, I Made; Waluyo, Untung; Fitriana, Eka; Suryani, Dewi (Universitas Negeri Makassar, 2020)
Abstract. This longitudinal study aims to seek for solutions concerning the teaching and learning English at the Faculty of Medicine University of Mataram (UNRAM). The first year of the study is emphasized on the outcomes of needs analysis, which encompasses the Present Situation Analysis (PSA), the Target Situation Analysis (TSA), and the Learning Situation Analysis (LSA). Various data were collected form the documents of Standar Kompetensi Dokter Indonesia (SKDI) a.k.a. Competency Standards of Medical Doctors in Indonesia, the Graduates Profile of Faculty of Medicine UNRAM and the documents of student English proficiency levels within the last 5 years. Other sources of data were taken from a number of focused group discussions and in-depth interviews with students, alumni, subject specialists, management of Block, and various techniques. The data were then analyzed descriptively and qualitatively. Findings of the study show that the level of English of students at Medical Faculty was still far from being adequate to meet the SKDI. As such, three learning goals were generated from this study, i.e. the short-tem, mid-term, and long-term goals. The study suggests that to bridge the gap, the Faculty of Medicine needs to develop a number of language programs to prepare these students to achieve competencies that meet the standard of Graduate Profile and SKDI.